KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PENGAWAI DI KECAMATAN LUBUKLINGGAU SELATAN I DAN SELATAN II - Surajiyo, Surajiyo; Nasruddin, Nasruddin; Paleni, Herman (FEB Universitas Sam Ratulangi Manado, 2020)
This study aims to determine the effect of leadership on employee job satisfaction, work environment on employee job satisfaction, leadership on employee performance, work environment on employee performance, leadership on employee performance through job satisfaction as an intervening variable and work environment on employee performance through job satisfaction. as an intervening variable in Lubuklinggau Selatan I and Selatan II Districts. The initial design stages in this study were formulating research problems, making hypotheses, tracing references / literature as study material, making research instruments or questionnaires, distributing questionnaires and distributing questionnaires to 102 employees of Lubuklinggau Selatan I and Selatan II Districts, then to analyze data using regression test, partial test, Path analysis and Sobel test with the help of statistical analysis tools IBM SPSS 22 for windows. The results showed that leadership has a significant effect on employee job satisfaction with the tcount for the leadership variable of 2.024, with a significant 0.046. Work environment has a significant effect on employee job satisfaction with the tcount for the work environment variable is 2.464, with a significant 0.015. Leadership has a significant effect on employee performance with the tcount for the work environment variable amounting to 10.818, with a significant value of 0.000. The work environment has a significant effect on employee performance with that the tcount for the work environment variable is 3.643, with a significant 0.000. Leadership has a significant effect on employee performance through job satisfaction as an intervening variable with tcount (2,74) greater than ttable (1.98), so there is an influence between leadership on employee performance through job satisfaction as a mediating or intervening variable and work environment has a significant effect. on employee performance through job satisfaction as an intervening variable with tcount (5,56) greater than ttable (1.98), so there is a direct and indirect effect between work environment on employee performance through job satisfaction as a mediating or intervening variable. Keywords: Keywords: Leadership, Work Environment, Job Satisfaction, PerformanceLeadership, Work Environment, Job Satisfaction, Performance